Sociodemographic Characteristics Of Hypertension Patients As A Basis For Health Promotion Media Planning: A Study At Bambanglipuro Health Center - Mahardika Primadani; Meylsa Rima Kamilda; Yanuri Dwi Maharani (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
Hypertension is a major public health issue requiring continuous control efforts through health promotion at the primary care level. The effectiveness of interventions is heavily influenced by the alignment of communication strategies and media with the target audience's characteristics. This study aimed to analyze the sociodemographic characteristics of hypertension patients as a basis for planning health promotion media at Puskesmas Bambanglipuro. A quantitative descriptive design was used. The sample consisted of 100 hypertension patients registered at Puskesmas Bambanglipuro, selected through purposive sampling. Variables analyzed included gender, age, marital status, education level, occupation, monthly income, family history, comorbidities (diabetes mellitus), and health insurance ownership. Data were analyzed using univariate and descriptive bivariate methods with the Chi-Square test (Continuity Correction) to observe the difference in educational proportions based on age groups.The majority of hypertension patients were female (74.0%) and dominated by the elderly group aged  ≥ 60 years (78.0%). Most respondents had a low level of education (67.0%), earned below the regional minimum wage (91.0%), and worked in the informal sector. The Chi-Square test showed a statistically significant difference in education level proportions between the elderly and adult groups (p-value = 0.029). All respondents (100%) had a family history of hypertension, and the vast majority owned health insurance (94.0%). The characteristics of hypertension patients, dominated by the elderly with low education and literacy levels that are statistically significantly lower, require a specific educational approach. Health promotion media planning at Puskesmas Bambanglipuro should emphasize a simple visual approach, interpersonal communication supported by visual aids, and active family involvement to optimize the utilization of health insurance in hypertension control.